Juventudes e instituições de acolhimento: o processo de desligamento e a percepção do viver em abrigo - Santos, Raiane de Jesus (2023)
The present study focuses on two variants: public policies for youth and reception institutions. The articulation of these categories occurred through a certain limitation observed in studies that deal with this topic in its entirety. It is important to remember that a considerable part of the academic productions focusing on these axes are concentrated in the areas of social work, psychology and also law. In the state of Sergipe, especially in the municipality of Aracaju, whose empirical focus was concentrated, no research was found that dealt with the process of disengaging young people from foster care institutions, further encouraging interest in delving into this field. In this sense, the respective work aimed to understand how foster care is experienced by young people and, mainly, how the institutional separation process occurs due to the age of civil majority. Starting from the understanding of youth as a social category, I sought to outline the historical context of the institutionalization of children and adolescents in Brazil, articulating this scenario with the perspective of public policies aimed at youth. The research was carried out using a qualitative approach in conjunction with some methodological tools, such as bibliographical research, documentary research and interviews. This last stage was divided into two moments: with the technical team from Abrigo Caçula Barreto and later with the young women who lived in the institutional republic for young people in foster care. The analysis and discussion of the data obtained from the research allows us to verify that the process of dismissal of young people who reach the age of majority in shelter units is much closer to a transition of spaces (from the shelter or home to the republic) than a de facto shutdown condition. These results were verified based on the theoreticalmethodological support used, however, the main guiding thread was directed to the narratives and subjectivities expressed by young people responsible for experiencing the foster care experience in different contexts and modalities.